2021
DOI: 10.1111/nyas.14608
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent birth and child undernutrition: an analysis of demographic and health surveys in Bangladesh, 1996–2017

Abstract: Adolescent birth is a major global concern owing to its adverse effects on maternal and child health. We assessed trends in adolescent birth and examined its associations with child undernutrition in Bangladesh using data from seven rounds of Demographic and Health Surveys (1996-2017, n = 12,006 primiparous women with living children <5 years old). Adolescent birth (10-19 years old) declined slowly, from 84% in 1996 to 71% in 2017. Compared with adult mothers (≥20 years old), young adolescent mothers (10-15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Most adolescent mothers were aged between 15 and 19 years, to the detriment of the age group between 10 and 14 years. A study conducted in Bangladesh between 1996 and 2017 showed similar proportions, with the majority of adolescents between the ages of 16 and 19 (NGUYEN et al, 2021). Furthermore, the present study also showed that neonatal deaths were predominant among mothers of the aforementioned age.…”
Section: Discussionsupporting
confidence: 80%
“…Most adolescent mothers were aged between 15 and 19 years, to the detriment of the age group between 10 and 14 years. A study conducted in Bangladesh between 1996 and 2017 showed similar proportions, with the majority of adolescents between the ages of 16 and 19 (NGUYEN et al, 2021). Furthermore, the present study also showed that neonatal deaths were predominant among mothers of the aforementioned age.…”
Section: Discussionsupporting
confidence: 80%
“…Pregnancy during adolescence leads to a struggle for nutrition between the mother and the fetus she is carrying. It generates nutritional deficiency condition that results in low birth weight or other conditions that is potentially impactful in the future (Nguyen et al, 2021). The results of the cohort study indicates that children born to adolescent mothers are shorter than children born to adult mothers.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately half of studies from Asia (6/11) (Ahmed et al, 2012;Fuada et al, 2020;Hossain et al, 2020;Mashal et al, 2008;Ngoc Hien & Ngoc Hoa, 2009;Nguyen et al, 2017) Nine studies in the qualitative synthesis presented data on moderate wasting in Asia (Ahmed et al, 2012;Akseer et al, 2018;Ali et al, 2019;Fuada et al, 2020;Hien & Kam, 2008;Mashal et al, 2008;Ngoc Hien & Ngoc Hoa, 2009;Nguyen et al, 2017Nguyen et al, , 2021 and 11 in SSA (Beiersmann et al, 2013;Boah et al, 2019;Friebert et al, 2017;Gbadamosi et al, 2017;Gewa & Yandell, 2012;Ickes et al, 2015;Issah et al, 2022;Mokwena & Kachabe, 2022;Olodu et al, 2019;Poda et al, 2017;Sobkoviak et al, 2012). For Asia, two-thirds of studies (6/9) reported an association between adolescent versus adult pregnancy and an increased risk of child wasting compared to approximately a quarter (3/11) of studies for SSA.…”
Section: Outcomes By Geographic Locationmentioning
confidence: 99%
“…Of the seven studies that measured maternal nutritional status, 5/7 with maternal BMI measurements observed that a greater proportion of adolescent mothers were underweight than their adult counterparts or had, on average, lower BMIs (Akseer et al, 2018;Das et al, 2022;Nguyen et al, 2017Nguyen et al, , 2019Nguyen et al, , 2021. In a cohort of adolescent mothers, conditional height-for-age z-score between 12 and 15 years of age was identified as a predictor of WAZ in the offspring between zero and 78 months (β 0.34 p < 0.05 in analysis including maternal anthropometry at two time points; β 0.41 p < 0.01 for analysis including maternal anthropometry at one time point).…”
Section: Influence Of Other Factorsmentioning
confidence: 99%